Sedem (židovských) problémov: Sociálna kultúra židovskej komunity z pohľadu etnológie - Salner, Peter (Ethnological studies, 2022)
Title in English: Seven (Jewish) problems: Social culture of the Jewish community from the perspective of ethnology. Based on his long-term research, the author presents a professional and personal perspective on selected problems of the contemporary Jewish community in Slovakia in the seven chapters of his book. The author devotes ample space to how the Jewish community reflected two totalitarian systems (the Holocaust and the period of Communism). He also notes the specificity of ethnological research, voluntary and forced migration processes, the issue of abandoned synagogues and cemeteries, or the phenomenon of "Jewish time." The book's final parts focus on social culture's problems (identity development, Jewish family, humor).